Pengaruh Komisaris Independen Dan Komite Audit Terhadap Audit Delay (Studi Kasus Pada Indeks Saham LQ-45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021) - Hesti Elmania; Febriyanto; Ardiansyah Japlani (Universitas Muhammadiyah Metro, 2024)
Based on the tests that have been carried out by the researchers using the requirements analysis test using the requirements analysis test (descriptive statistical analysis and normality test), testing the classical assumptions regression requirements using (multicollinearity test, autocorrelation test, heteroscedasticity test) and hypothesis testing using (t test , F test and R2 determination test) the results show that the independent commissioner has a positive and significant effect on audit delay and the audit committee also has a positive and significant effect on audit delay and the simultaneous test shows that the independent commissioner and audit committee have a joint effect on audit delay on the LQ-45 stock index listed on the Indonesia Stock Exchange from 2019 to 2021.